Discovery of Buprestidae rock art in central Iran suggests historical relationship between jewel beetles and mankind. Issue 2 (25th March 2020) - Kolnegari, Mahmood; Naserifard, Mohammad; Hazrati, Mandana
Abstract: An extensive field survey was undertaken by a group of archaeologists and entomologists to discover arthropod‐like petroglyphs in the center of Iran during 2017 to 2018. A remarkable motif approximately 13 × 5 cm in size was found in the Teymareh rock art site, located in Markazi province, which has yet to be reported. The single rock art distinctly represents a hexapod organism with small antenna, a streaked narrow body and a tapering abdomen. Based on distinguishing aspects of the inspected motif and morphological information of species within the class Insecta, we identified it as a jewel beetle (Coleoptera: Buprestidae). We propose that the buprestid drawing was derived from a historic artist who admired the aesthetic value of the jewel beetle. The jewel beetle's characters within Persian Plateau folklore are also briefly discussed. Abstract : We as entomologists and archaeologists discovered an ancient petroglyph representing a jewel beetle. This finding could show the current relationship between humankind and jewel beetles dates back to the prehistoric era.